PENGARUH QUICK RATIO, INVENTORY TURNOVER DAN DEBT TO EQUITY RATIO TERHADAP RENTABILITAS PADA PERUSAHAAN KABEL YANG TERDAFTAR DI BURSA EFEK INDONESIA - Nurul Fadilah; Echsan Ghani; Evaliati Amaniyah (Kompetensi (Competence : Journal of Management Studies), 2017)
The purpose of study is to determine the effect of Quick Ratio, Inventory Turnover and Debt to Equity Ratio  to Profitability on cable companies listed in Indonesia Stock Exchange. This study  use quantitative method. Based on purposive sampling method,  the are 6 companies in cable sector as sample. The multiple liniear regression analysis is used to test  the hypothesis. The result of this study indicate that  all independent variables don’t affect simultans to Profitability while in partial Quick Ratio, Inventory Turnover and Debt to Equity Ratio don’t affect to Profitability. the coefficient of determination (R2) in this study is 6.1%, it means that the independent variables used in this study can explain the dependent variable  6.1% and the rest 93, 9% is explained by other variables that are not used in this study.